2015
DOI: 10.1080/09593330.2014.993728
|View full text |Cite
|
Sign up to set email alerts
|

Co-composting of horticultural waste with fruit peels, food waste, and soybean residues

Abstract: Horticultural waste was co-composted with fruit peels, food waste, and soybean residues individually to evaluate the effects of these easily available organic wastes in Singapore on the composting process and product quality. Each co-composting material was mixed with horticultural waste in the wet weight ratio of 1:1 and composted for 46 days. Results showed that all co-composting materials accelerated the degradation of total carbon and resulted in higher nutrients of nitrogen (N), phosphorous (P), and potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The concentrations of zinc (Zn) and Fe were 0.59 and 1.62 mg/kg, respectively, across all growing media. Fe content in plant tissues was higher compared with the contents of Cu, Zn, and Pb, which are similar to the results reported by Chiroma et al (2012). This could be due to the high possibility of Fe strategizing its translocation from the growing medium to the plant tissue, mainly on the interaction of ferric chelate reductase, which ended up mostly in the leaf chloroplast (Jeong and Connolly 2009).…”
Section: Accumulation Of Heavy Metals In Plant Tissuesupporting
confidence: 87%
See 1 more Smart Citation
“…The concentrations of zinc (Zn) and Fe were 0.59 and 1.62 mg/kg, respectively, across all growing media. Fe content in plant tissues was higher compared with the contents of Cu, Zn, and Pb, which are similar to the results reported by Chiroma et al (2012). This could be due to the high possibility of Fe strategizing its translocation from the growing medium to the plant tissue, mainly on the interaction of ferric chelate reductase, which ended up mostly in the leaf chloroplast (Jeong and Connolly 2009).…”
Section: Accumulation Of Heavy Metals In Plant Tissuesupporting
confidence: 87%
“…Various factors may, however, contribute to the quality of FW compost as the sources of FW vary by their heterogeneous compositions, sources, and the eating habits of 1 3 consumers (Cerda et al 2018). Several studies have concluded that when FW compost is applied as soil additive, it promotes plant growth and improves biomass and nutrition provision (Choy et al 2015;Ronga et al 2016;Kaur et al 2017). Nevertheless, the quality of the food compost produced depends on various factors, such as moisture content, carbon and nitrogen ratio, aeration, porosity, bulk density, and organic matter (Azim et al 2018;Waqas et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The pH of the hop biomass mature compost falls within this range at 7.8, while the pH of the hop biomass input material is around 6.5. Similar increase in pH has been observed in horticultural waste composting, as reported by Choy et al [11]. Despite these general trends, it is important to note that the pH requirements of specific plants may vary [12].…”
Section: Hop Biomass Compost Characteristicssupporting
confidence: 82%
“…In recent decades, compost application is one of the major interesting research subjects due to increasing awareness of waste management (Petrus et al 2010;Choy et al 2015). Therefore, the abundance of agricultural waste such as rice straw (RS) in paddy industry can be effectively transformed and converted into organic fertilizer via the composting process.…”
Section: Introductionmentioning
confidence: 99%